Risk assessment for human metal exposures : mode of action and kinetic approaches - Nordberg, Gunnar; Fowler, Bruce A. (Academic Press, 2018)
Risk Assessment for Human Metal Exposures: Mode of Action and Kinetic Approaches examines the current principles of risk assessment in human metal exposures, with a focus on Mode of Action(MOA), Toxicokinetic and Toxicodynamic (TKTD) considerations, and computer models. Derived from the highly respected Handbook on the Toxicology of Metals, Fourth Edition (2014), the book summarizes principles and methods and provides examples of how MOA -TKTD can be used. In addition, it presents tactics on how information generated by such methods can be confirmed by epidemiological data. Furthermore, it demonstrates how epidemiological data can be confirmed and evaluated by the examined models and considerations. This resource uniquely integrates several important topics, such as risk assessment, characterization, management and communication-the classic risk assessment paradigm-with mode of action, TKTD, and epidemiology, all topics related to human exposure. Written by pioneers in the field, this book is an essential reference for researchers, students and technicians in toxicology and risk assessment.